Digitalisasi Informasi di Museum Muhammadiyah Yogyakarta Sebagai Sarana Inovasi dan Teknologi di Era Digital 5.0 - Ahsin, Kahfie Ahmad; Warto; Haniati, Umi (Al-Ma mun Jurnal Kajian Kepustakawanan dan Informasi, 2025)
Museums, as institutions preserving historical heritage, face significant challenges in the era of Digital 5.0, where innovation and technology are essential for conveying religious and academic values to the broader society. This study examines the digitalization information at the Muhammadiyah Museum in Yogyakarta, focusing on the innovation of historical information systems as a means of revitalizing ushuluddin values. A qualitative descriptive method is employed, using literature studies and documentation as the primary sources. The findings reveal that digitalization not only facilitates broader access to the Islamic historical narratives promoted by Muhammadiyah but also strengthens the transmission of Islamic values to younger generations in a contextual and interactive manner. This innovation transforms the museum from a mere physical space into a relevant medium for cultural da'wah in an era of digital transformation   Keywords: museum digitalization, Islamic information, Muhammadiyah Museum, historical information system, Digital 5.0 era